AMBIVALENCE OF INTEGRATED MYSELF - DESINTEGRATED MYSELF IN ADOLESCENCE - T. M. Zelins'ka (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2014)
A systemic formative psychological phenomenon (integrated myself - desintegrated myself) is a semantic integrity and «a system of systems» in the structure of the genesis of personal ambivalence in adolescence. Integrated myself and desintegrated myself are linked to each component of ambivalence as a whole with one of several of its major units. The need in life as the root cause of personality development (S. D. Maksimenko) has a stable branch in the ambivalence of integrated myself and desintegrated myself in adolescence. Integrated myself has a moderate resistance to a different expression of oneself, characterized by balance, coherence and harmony experiences in adolescence. Desintegrated myself is characterized by an intense expression of resistance and struggle for dominance of different aspects of oneself and suppression of others which is accompanied by imbalances, inconsistencies and disharmony of experience at this age. It has been shown that the expressions of ambivalence of integrated myself - desintegrated myself in those adolescents are found in three levels: low harmonic, average inconsistent and high disharmonious. It has been found that there is a gradual increase in low harmonic level in persons from 17 to 20 years old. In addition, it has been found that there is a positive gradual reduction of average inconsistent and high disharmonious levels among people of 17 to 20 years old. The study has found that there is an increase of imbalance, incoherence, disharmony in ambivalence of integrated myself - desintegrated myself and wish to change during the transition to early adulthood among persons of 21 years old.